Predictors of Students` Desire to be an Entrepreneur: Kyrgyzstan, Georgia, and the United States - Barry A. FRIEDMAN; Nergis AZIZ; Ibrahim KELES; Salavat SAYFULLIN (Eurasian Journal of Business and Economics, 2012)
Entrepreneurship is an important element of national economic growth, and college business students represent an important feeder pool for a nation’s supply of entrepreneurs. The purpose of this study is to identify and contrast predictors of students’ desire to be entrepreneurs in Kyrgyzstan, Georgia, and the United States. Three hundred and five undergraduate business students in Kyrgyzstan, Georgia, and the United States completed the Aspiring Entrepreneurial Motives Questionnaire (Aziz, Friedman & Sayfullin, 2012). While the recognition motive was important for all students, predictors of their desire to be entrepreneurs differed across the three countries. In contrast to Kyrgyzstan and the United States, students’ in Georgia overall desire to be entrepreneurs was more complex as finance, recognition, freedom, marketing opportunities and economic conditions reached significance. National initiatives that recognize entrepreneurial accomplishments may therefore encourage more individuals to start and manage businesses. A more complex strategy may be required in Georgia, as the decision to be an entrepreneur appeared to be more multidimensional.